(untitled) (Bangladesh Journal of Botany, 2015)
Stem and leaf anatomy of Origanum rotundifolium Boiss., O. vulgare L. ssp. viride (Boiss.) Hayek, Teucrium hircanum L., belonging to Lamiaceae were characterized and compared. Some important differences were determined in the taxa. In addition, trichome diversity was investigated by light microscopy and three main types of trichomes (peltate, capitate glandular and non-glandular) were observed in three taxa. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21612 Bangladesh J. Bot. 43(3): 345-352, 2014 (December)